Financial Performance Analysis Using Inventory Turn Over Ratio, Receivable Turn Over Ratio, and Fixed Asset Turn Over Ratio - Desta Riany; Nor Norisanti; Kokom Komariah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
In the cement sub-sector company on the Indonesia Stock Exchange from 2015 to 2018 cement sales increased but the profits that were earned always decreased. Activities in the company have an important role so that the company's financial performance is in good condition. The purpose of this study is to determine the company's financial performance in terms of its activities. The research method used is quantitative. The data analysis technique used is horizontal analysis with inventory turnover ratio, receivable turnover ratio, and fixed asset turnover ratio. The result of this research is that the decline in the company's financial performance is seen from inventory turnover, receivable turnover, and fixed asset turnover.